Hubungan Status Ekonomi Dan Partisipasi Keluarga Dengan Pertumbuhan Anak Balita Di Wilayah Perkotaan Kabupaten Berau - Andy Nuriyanto (ECO-BUILD, 2025)
Background: Growth problems along with child nutrition problems are public health problems that have a multifactorial impact on the quality of life of children as the next generation of the nation. The impact of lack of participation and ability of parents in fulfilling and caring for children's growth and development has the potential to become a problem biologically, socially, psychologically, and in maintaining health. Aim: This study aims to analyze the relationship between economic status and family participation with the growth of toddlers in the Urban Area of ​​Berau Regency. Method: Quantitative correlational design with a cross-sectional approach with 159 family samples with toddlers. The instrument used a questionnaire and the Healthy Menu Card. Data analysis was carried out using the Fisher Exact Test with a significance level of 0.05. Results: Most of the respondents in this study had middle economic status (n = 96; 60.4%). Almost half of the respondents were dominated by Good Participation (n = 64; 40.3%). Most children had Normal development status (n = 89; 56.0%). There is a significant relationship between economic status (p-value 0.000; coeff corr 0.635) and Family Participation (p-value 0.000; coeff corr 0.583) with the growth of toddlers in the Urban Area of ​​Berau Regency. Conclusion: The better the economic status and family participation, the better the growth status of toddlers